A Racism in Consumer Practices and its Communicative and midiatic sphere: an inquire based on latin american media theory - Ferreira, Ronaldo Ribeiro (Anais de Artigos do Seminário Internacional de Pesquisas em Midiatização e Processos Sociais, 2024)
Based on the recognition of racism as a relevant social marker in Brazilian society, this work presents a contribution that allows us to problematize this phenomenon within the framework of the communication and consumption interface. To this end, it is theoretically based on studies of the Latin American tradition of communication, especially with regard to the concepts of mediation and mediatization to find a possible epistemological delimitation: racism as a communicational phenomenon, linked to a long historical trajectory and the racism as a media phenomenon. In summary, it presents the hypothesis, exemplified in the case of Brazilian advertising, that both dimensions, although interdependent and dialectically determined, have their own processes and dynamics.